Interrater Reliability Reviewed By Many Rater - Destiniar, Destiniar (Jurnal Dosen Universitas PGRI Palembang)
Abstract: The purpose of this study is to see which one is better both the interrater reliability coefficients were rated by 18 rater or 6 rater and analyzed by the Fleiss Kappa method.Instrument that is assessed in the form of Mathematic test for the nineth grade made by the teacher in the form of multiple choice with 4 options. The method used experimental method and data is processed by using t-test. The results obtained show that the interater reliability coefficient of the Mathematic test for nineth grade analyzed by the Fleiss Kappa method and rated by 18 rater was higher than that assessed by the 6 rater. key words: Reliabilitas Interrater, Fleiss Kappa Reliabilitas Interrater, Thepurpose of this study is to see which one is better bothFleiss Kappa the interrater reliability coefficients were rated by 18 rater or 6 rater and analyzed by the Fleiss Kappa method. Instrument that is assessed in the form of Mathematic testfor the nineth grade made by the teacher in the form of multiple choice with 4 options. The method used experimental method and data is processed by using t-test. The results obtained show that the interater reliability coefficient of the Mathematic test for nineth grade analyzed by the Fleiss Kappa method and rated by 18 rater was higher than that assessed by the 6 rater.